Pola Komunikasi Dan Pengetahuan Gizi Ibu Dan Anak Dalam Praktiknya Di Desa Kedung Pengawas - Desryanto, Panji Nuzul; Endah, Sari (Jurnal Ilmiah Wahana Pendidikan, 2024)
Parents, especially mothers, have an important role in maintaining the quality of children's food to monitor the nutritional value contained in food. This is very important to note, considering that nutrition is a necessity for children for the growth and development of children in the future. To realize this, it is necessary to have the right pattern of communication between mother and child. By using qualitative methods and interviewing several women in the village of Kedung Supervisor, the pattern of democratic communication is considered very appropriate because it does not make children feel pressured by the rules they get. And in this communication, children become more open with what they want without being afraid to reveal it to their mother. As for the constraints, there are external factors, namely friends of children who are still not disciplined in choosing food.